The Credentials of Brain-Based Learning - Davis, Andrew (Journal of Philosophy of Education, 2004)
This paper discusses the current fashion for brain-based learning, in which value-laden claims about learning are grounded in neurophysiology. It argues that brain science cannot have the ‘authority’ about learning that some seek to give it. It goes on to discuss whether the claim that brain science is relevant to learning involves a category mistake. The heart of the paper tries to show how the contribution of brain science to our grasp of the nature of learning is limited in principle. Finally the paper explores the potential of brain science to illuminate specific learning disabilities.